2019
DOI: 10.1021/acsami.8b22075
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Controlled in Situ Growth of Silver Microwires Forming Bioelectronic Interfaces

Abstract: There is a pressing need to advance our ability to construct three-dimensional (3D) functional bioelectronic interfaces. Additionally, to ease the transition to building cellular electronic systems, a remote approach to merge electrical components with biology is desirable. By combining 3D digital inkjet printing with bipolar electrochemistry, we remotely control and fabricate conductive wires, forming a first of its kind contactless bionic manufacturing procedure. It enables controlled fabrication of conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…Again, high- and low-impedance electrolytes of water and PBS, respectively, were used. We have previously shown that the short time frame of these experiments (<1 min) using water does not affect cell viability …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Again, high- and low-impedance electrolytes of water and PBS, respectively, were used. We have previously shown that the short time frame of these experiments (<1 min) using water does not affect cell viability …”
Section: Resultssupporting
confidence: 94%
“…We have recently reported on the development of a nanobioelectronic system that was based on using nanobipolar electrodes (nano-BPEs) in the presence of biological cells for the first time . This work was based on a “bipolar electrochemical system” (BES), which consists of bipolar electrodes (BPEs) and an aqueous electrolyte solution. Upon the application of an external electric field from feeder electrodes (FEs), the BPE becomes polarized.…”
Section: Introductionmentioning
confidence: 99%
“…A similar electrochemical approach has been used to generate conductive structures to dictyostelium cells; however, as the approach was not performed wirelessly, and the gap between electrodes was limited to <30 μm, this limits its application in bioelectronics in vivo (Thapa et al, 2009). The use of bipolar electrochemistry to wireless grow conductive structures greatly improves this prospect for in vivo applications; we have recently shown this possible in the presence of CHO cells (Sanjuan‐Alberte, Saleh, et al, 2019). This could have exciting applications in connecting specific cell populations to electronics, as well as for targeting electric field therapies or eliciting an electrochemical reaction.…”
Section: Wireless Nanobioelectronic Toolsmentioning
confidence: 99%
“…AuNP‐based systems are also able to provide novel bioelectronic approaches to sense intracellular electrical changes in response to externally applied electric potentials. Redox state of water soluble AuNPs modified porphyrin groups was modified intracellularly under the application of electrical potentials (Sanjuan‐Alberte et al, 2019). With further optimization, possibly through the use of AC currents, and understanding of how this phenomena performs at the nanoscale, it may be possible to develop tools with the ability to modulate chemistry inside cells under external electric fields (A. Robinson et al, 2020).…”
Section: Wireless Nanobioelectronic Toolsmentioning
confidence: 99%
“…We have recently reported on the development of a nanobioelectronic system that was based on using nanobipolar electrodes (nano-BPEs) in the presence of biological cells for the first time. 5 This work was based on a "bipolar electrochemical system" (BES), which consists of bipolar electrodes (BPEs) and an aqueous electrolyte solution. 6−9 Upon the application of an external electric field from feeder electrodes (FEs), the BPE becomes polarized.…”
Section: ■ Introductionmentioning
confidence: 99%